2017
DOI: 10.1111/bjd.15693
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival of methotrexate in psoriasis

Abstract: Linked Article: Otero et al. Br J Dermatol 2017; 177:497–504.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Drug survival estimates for methotrexate, for example, also vary considerably—likely indicating variable long-term tolerability. Data from a prospective Dutch registry of patients treated with methotrexate (MTX-CAPTURE) showed drug survival rates of 63%, 30% and 15% after 1, 3 and 5 years, respectively; the median drug survival was 1.8 years [ 166 , 171 ]. Other studies showed the duration of the first treatment course to be, on average, 18.8 months [ 135 ] and that 68% of patients discontinued methotrexate after an average of ~ 4.2 months [ 172 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drug survival estimates for methotrexate, for example, also vary considerably—likely indicating variable long-term tolerability. Data from a prospective Dutch registry of patients treated with methotrexate (MTX-CAPTURE) showed drug survival rates of 63%, 30% and 15% after 1, 3 and 5 years, respectively; the median drug survival was 1.8 years [ 166 , 171 ]. Other studies showed the duration of the first treatment course to be, on average, 18.8 months [ 135 ] and that 68% of patients discontinued methotrexate after an average of ~ 4.2 months [ 172 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] MTX as a traditional drug is recommended as induction and long-term treatment for moderate-to-severe PV and PsA. [ 2 3 ] MTX causes an inhibition of the inflammatory response by activating adenosine receptors, such as the A2A receptor. [ 4 ] Furthermore, MTX is believed to decrease the nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-κΒ) activity and interleukin (IL)-17 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate (4-Amino-10-methylfolic acid hydrate, MTX) is an antagonist of folic acid (pteroyl-L-glutamic acid, FA) that is commonly prescribed in the treatment of various neoplastic disorders (1)(2)(3)(4), ectopic pregnancies, dermatologic conditions, voluntary early foetal terminations (5)(6)(7) and several inflammatory diseases such as psoriasis, psoriatic arthritis, inflammatory bowel disease and rheumatoid arthritis (8) systemic lupus erythematosus and juvenile arthritis (9). The use of MTX can be associated with side effects affecting various organs including stomach, intestine, haematologic system, liver, lung and central nervous system (10)(11)(12)(13)(14) which is experienced by almost one-third of the patients (15).…”
Section: Introductionmentioning
confidence: 99%